CHUST: A CITY OF ANCIENT TRADITIONS (Ustozlar uchun, 2024)
Annotation. This article, written by Oynura, a 9th-grade student from Chust, Namangan, explores the rich history and cultural heritage of Chust. Known for its exceptional craftsmanship in knife-making and metalworking, Chust has evolved into a popular tourist destination with beautiful parks and traditional teahouses. The article highlights the city's famous palov, a beloved Central Asian dish, and delves into Chust's historical sites, cultural significance, and modern development. It emphasizes the blend of tradition and progress that characterizes Chust, making it a unique and vibrant community.